Dissolution of Thermoelectric Materials Containing Te with Acidic Solutions - Lee, Hwa Young; Lee, Joong Kee (TAYLOR & FRANCIS INC, 2015)
An attempt to dissolve thermoelectric materials such as Bi2Te3 and Sb2Te3 has been made with acidic solutions in order to separate tellurium from those materials. The chemical reagents of Bi2Te3 and Sb2Te3 were used for the dissolution tests. As a result, it was found that percent extraction of Te increased considerably with the concentration of nitric acid in the presence of hydrogen peroxide when Bi2Te3 was dissolved with nitric acid. It was found that the addition of oxidizing agent such as hydrogen peroxide may be essential for dissolution of Bi2Te3 with acidic solutions. It was also remarkable that percent extraction of Sb was extremely lower than that of Te when Sb2Te3 was dissolved by nitric acid. As far as the effect of temperature on dissolution of Sb2Te3 was concerned, extraction of Te was considerably increased with increase in temperature.
Keywords: EXTRACTION; TELLURIUM; SEPARATION; CADMIUM; RECOVERY; KINETICS; WASTE